FACTORS INFLUENCING NETFLIX PURCHASE INTENTION IN JAKARTA - Devia Megasari; Sanny Ekawati (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this research is to determine the influence of service quality, trust, and e-payment on purchase intention for Netflix streaming services in Jakarta. The research design utilized is causal with a quantitative approach. The instrument for this research is a questionnaire in a Google form which is distributed via social media. The sample size was 180 respondents who were Netflix users in Jakarta. The sample selection technique in this research was carried out using a purposive sampling technique. Data analysis used SmartPLS software version 4.0. Data analysis consists of outer and inner models. The outer model includes validity and reliability tests, while the inner model includes R-square, Q-square, f-square test, GoF test, path analysis, and hypothesis tests. The outcomes about of this research appear that service quality, trust, and e-payment have a significant positive effect on purchase intention on the Netflix streaming service in Jakarta.